Coming of age in Khayelitsha: gendered identity, sexual partnerships and the transition to adulthood - Swartz, Alison (Department of Public Health and Family Medicine, 2017)
The lives of young people in Khayelitsha are characterised by a series of intersecting challenges. These include inadequate access to education, limited opportunities to find gainful employment, exposure to violence and the risk of contracting HIV. Several conventional avenues of transition to adulthood, for example achieving financial independence, moving out of the parental home or getting married, remain unavailable to many. The majority thus find themselves in a situation of waithood, an interminable period between childhood and adulthood characterised by extreme uncertainty. This thesis takes up questions of what it means to be a young man or woman navigating towards adulthood in this context of socioeconomic marginalisation. In particular, it explores the ways that youth negotiate the tensions between the structures that shape their lives and their opportunities for agency within the domains of gendered identities and sexual partnerships. Public health research and intervention with youth tends to rely more heavily on approaches underpinned by individual-level behaviour change theories, with lesser albeit growing attention paid to the structural forces that shape young lives. This thesis aims to balance the reading of individuals' capacity for agency in decision-making, with the broader structural forces that shape their life trajectories. To this end, a longitudinal, ethnographic approach was employed to capture nuances of context and experience as they unfolded and shifted through time and space. The data presented here is drawn from 18 months of ethnographic fieldwork with young people in the neighbourhood of Town Two, Khayelitsha, primarily collected between 2014 and 2015. Youth transition to adulthood is explored in the two interrelated domains of gendered identity and sexual partnerships. Within these domains, living up to individual and social ideals associated with masculinity and femininity is persistently challenging. Faced with these challenges, young people employ creative and dynamic strategies in their endeavours to maximize the precarious gains they make in their transition towards adulthood. Broadly speaking, these strategies include those linked to their physical bodies, sexual and social networks and the ways that they invoke ideas about what it means to be a young South African citizen. The findings highlight that in their transitions to adulthood, youth in Khayelitsha are neither complete victims, nor entirely free agents with the capacity to radically change their circumstances. This thesis ends by offering some recommendations about how public health programming might take into account the lived experiences of youth as they navigate the transition to adulthood in this context.